Thomas Kuhn - Nickles, Thomas, 1943- (New York : Cambridge University Press, 2003)
Offers an introduction to the life and work of scientific philosopher Thomas Kuhn, discussing his fundamental theories and their applications to modern science.
Includes bibliographical references (p. 282-284) and index.
Adult
Keywords: Kuhn, Thomas S; Kuhn, Thomas S; Science -- Philosophy; Science -- Philosophy